Body roundness index: superior predictors of intramuscular fat infiltration in general population - Yu, Rui; Wang, Yu; Zhang, Yiping; Gao, Xifa; Zhang, Dingzhe; Wang, Jianhua; Chen, Xiao (Frontiers in Nutrition, 2026)
BackgroundBody mass index (BMI) could not exactly reflect body fat distribution. Body Roundness Index (BRI) may be a better marker reflecting the ratio of total body fat to visceral fat. This study aimed to show the association between BRI and intramuscular fat infiltration (IMFI), and compare the ability of the BRI and BMI to predict IMFI in general populations.MethodsThe assessment of IMFI was conducted via both computed tomography (CT) and magnetic resonance imaging (MRI). In the CT cohort, IMFI was defined as CT attenuation < 37.5 Hounsfield Unit. In the MRI cohort, the IMFI was evaluated by fat fraction. Those with a fat fraction higher than the third quartile of the overall population were defined as the IMFI. Logistic regression analysis, Spearman’s correlation, stratified analysis, and receiver operating characteristic (ROC) curve analysis were performed to investigate the associations between BMI, BRI and the IMFI.ResultsA total of 1,268 participants were included in the CT cohort and 198 subjects in MRI cohort. The subjects with high BRI (≥5.5) had higher prevalence of IMFI than those with BRI < 5.5 (67.3% vs. 25.4%, p < 0.001). BRI and BMI was both associated with an increased risk of IMFI in CT cohort [odds ratio (OR) = 1.96, 95%confidence interval (CI): 1.55–2.49; OR = 1.20, 95%CI: 1.13–1.28]. Similar trends were observed between high and low BRI and BMI quartiles groups. Spearman’s correlation revealed that the BRI was associated with muscle density, muscle fat fraction and handgrip strength in both men and women. The ROC curve revealed that the BRI had a better ability to predict the risk of IMFI than BMI (p < 0.05) in both CT and MRI cohort.ConclusionCompared with BMI, the BRI is a better index to evaluate the IMFI, especially in the female population.